A comparison between beta titanium wire, nickel titanium wire and stainless steel wire as distal spring of pendulum - Panurat Limpasirisuwan (Prince of Songkla University, 2011)
Thesis (M.Sc., Oral Health Sciences)--Prince of Songkla University, 2009